Region of origin diversity in immigrant health: Moving beyond the Mexican case. (October 2016) - Reynolds, Megan M.; Chernenko, Alla; Read, Jen'nan Ghazal
Abstract: Research suggests that Mexican immigrants arrive in the United States with equivalent or better health than native-born whites but lose their advantage over time. We seek to examine systematically how well the patterns of initial advantage and deteriorating health apply to immigrants originating from other regions of the world – regions that represent a growing proportion of U.S. immigrants. We begin by identifying which of the groups in our study have a health advantage compared to U.S.-born whites and to Mexican immigrants. We then we assess changes in health over time, controlling for variation in the health profiles of cohorts upon arrival. We use logistic regression of self-rated health and heart conditions with data from the 2004–2013 National Health Interview Survey. The results reveal diversity and similarity in health outcomes across world regions of origin, both on arrival and over time. By comparing and contrasting cases previously examined in isolation, we clarify and qualify theories of the immigrant health paradox and health deterioration. Highlights: Immigrants across regions generally arrive in better health than U.S.-born whites. Non-Mexican-born and Mexican-born health profiles are both alike and different. Findings for Mexican immigrants do not universally apply to other populations.